Morphological parameters of nanoparticles used in nano lubrication - a review. Issue 1 (June 2021) - Singh, Anoop Pratap; Tripathi, Ajay; Shukla, Matsyendra Nath; Suhane, Amit
Abstract: Nanotechnology provides a lot of progress in all areas of engineering and technology. Similarly, in the field of lubrication, nano particles play vital role. It has been intensively evaluated in the last many years. Nano particles capable of improving the performance of lubricating oil. This review summarizes the morphological parameters of nanoparticles in the field of oil lubrication. Researchers studies various shapes, sizes and compositions of nanoparticles. This review is able to provide information about the morphological parameters of nanoparticles for better understanding of nano lubrication.